STUDI PENGALAMAN GURU DALAM MENERAPKAN PEMBELAJARAN BERDIFERENSIASI DI KELAS 2 SDN PAKULONAN 2 KOTA TANGERANG SELATAN - Dinda Habsah; Ina Magdalena; Rizki Zuliani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research focuses on how a second-grade teacher at SDN Pakulonan 2, South Tangerang City, carries out differentiated learning practices in daily classroom activities. Using a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews with the teacher and principal, and a review of instructional documents. The findings show that the teacher consistently conducts diagnostic assessments to identify students’ readiness, interests, and learning styles. This information then serves as the foundation for designing content, processes, and learning products that meet the needs of each individual student. Nevertheless, this practice faces several challenges, such as limited time, diverse student abilities, and a lack of supporting facilities. Interestingly, the teacher does not stop at these obstacles but instead develops adaptive strategies such as student grouping, the use of simple media, and collaboration with colleagues. These findings affirm that differentiated learning is not merely a concept within the Merdeka Curriculum, but can be genuinely implemented in primary classrooms. Furthermore, this study makes an important contribution to strengthening inclusive education practices that place every child at the center of the learning process.